Seasonality and interannual variability of an Arctic marine time series, IsA - Anna Vader; Eleanor Handler; Ragnheid Skogseth; Aud Larsen; Tove M. Gabrielsen (Arctic Science, 2025)
The Arctic is warming twice as fast as anywhere else on the planet, in the European Arctic mainly driven by exalted Atlantic Water inflow. Microbial eukaryotes are diverse and essential to the functioning of marine ecosystems, thus environmental perturbations altering their communities influence the entire ecosystem. To study seasonal and interannual variation and the potential effects of Atlantification, a long-term marine time series has been established in Isfjorden-Adventfjorden, West Spitsbergen. We here present 3 years of high-resolution data including hydrography, nutrients, photosynthetic biomass, flow cytometry and community composition of microbial eukaryotes (0.45–10 µm, based on Illumina metabarcoding of 18S rDNA and rRNA). The timing, magnitude and species composition of the spring bloom varied interannually, with the more Atlantic spring 2014 being distinctly different from the two other years. A strong recurring seasonal pattern was evident in biodiversity, cell abundances and community composition. Winter communities were characterized by high alpha diversity and very low cell numbers with a dominance of heterotrophic and parasitic taxa. Despite large intra- and interannual differences in communities during the productive time of the year, winter communities were always highly similar, suggesting that the polar night represents a strong environmental forcing that resets the microbial communities.